PERFORMANCE ANALYSIS OF GRAPH DATABASE AND RELATIONAL DATABASE - Agustian Prakarsya Mardin; RZ. Abdul Aziz; Ari Kurniawan (Proceeding International Conference on Information Technology and Business, 2020)
There were many database methods for managing data. They were widespread industries that had a huge success. The method used in this study was the relational database method and the graph database. The relational database method was considered as the standard for over thirty years. The graph database consisted of several components e.g., nodes, edges, and properties that represented the data storage. The graph database provided index-free adjacency, which meant that each element contained a direct pointer which was adjacent to the elements and no longer required an index lookup. These databases can be more scaled to the larger datasets as they generally did not require a